Amniotic fluid embolism and disseminated intravascular coagulation complicating hypertonic saline-induced abortion. Issue 688 (February 1983) - Ballas, S.; Lessing, J. B.; Michowitz, M.
Abstract : Amniotic fluid embolism (AFE) associated with disseminated intravascular clotting (DIC) is usually fatal. Such a combination generally occurs at the term of pregnancy or in the immediate postpartum period. A case of AFE with DIC following a hypertonic-saline-induced abortion, is reported. The patient was in the midtrimester with a live fetus. Prompt recognition and treatment of her condition ensured her complete recovery. Such a case has not, to our knowledge, been previously reported.